3D Modeling of Buildings : Outstanding Sites. - H. & eacute (GIS and Territorial Intelligence, 2014)
Relevant to anyone interested in high resolution 3D surveying, this book presents a state-of-the-art of the methods specifically adapted to outstanding sites and the research currently being carried out in this area. --